Tree diversity reduces pathogen damage in temperate forests: A systematic review and meta-analysis - Elsa Field; Andrew Hector; Nadia Barsoum; Julia Koricheva (Forest Ecology and Management, 2025)

Many unreported crop pests and pathogens are probably already present - Daniel P. Bebber; Elsa Field; Heng Gui; Peter Mortimer; Timothy Holmes; Sarah J. Gurr (Global Change Biology, 2019)
Invasive species threaten global biodiversity, food security and ecosystem function. Such incursions present challenges to agriculture where invasive species cause significant crop damage and require major economic investment to control production losses. Pest risk analysis (PRA) is key to prioritize agricultural biosecurity efforts, but is hampered by incomplete knowledge of current crop pest and pathogen distributions. Here, we develop predictive models of current pest distributions and test these models using new observations at subnational resolution. We apply generalized linear models (GLM) to estimate presence probabilities for 1,739 crop pests in the CABI pest distribution database. We test model predictions for 100 unobserved pest occurrences in the People's Republic of China (PRC), against observations of these pests abstracted from the Chinese literature. This resource has hitherto been omitted from databases on global pest distributions. Finally, we predict occurrences of all unobserved pests globally. Presence probability increases with host presence, presence in neighbouring regions, per capita GDP and global prevalence. Presence probability decreases with mean distance from coast and known host number per pest. The models are good predictors of pest presence in provinces of the PRC, with area under the ROC curve (AUC) values of 0.75–0.76. Large numbers of currently unobserved, but probably present pests (defined here as unreported pests with a predicted presence probability >0.75), are predicted in China, India, southern Brazil and some countries of the former USSR. We show that GLMs can predict presences of pseudoabsent pests at subnational resolution. The Chinese literature has been largely inaccessible to Western academia but contains important information that can support PRA. Prior studies have often assumed that unreported pests in a global distribution database represent a true absence. Our analysis provides a method for quantifying pseudoabsences to enable improved PRA and species distribution modelling.

Herbivore control of annual grassland composition in current and future environments - Halton A. Peters; Elsa E. Cleland; Harold A. Mooney; Christopher B. Field (Ecology Letters, 2006)
Selective consumption by herbivores influences the composition and structure of a range of plant communities. Anthropogenically driven global environmental changes, including increased atmospheric carbon dioxide (CO 2 ), warming, increased precipitation, and increased N deposition, directly alter plant physiological properties, which may in turn modify herbivore consumption patterns. In this study, we tested the hypothesis that responses of annual grassland composition to global changes can be predicted exclusively from environmentally induced changes in the consumption patterns of a group of widespread herbivores, the terrestrial gastropods. This was done by: (1) assessing gastropod impacts on grassland composition under ambient conditions; (2) quantifying environmentally induced changes in gastropod feeding behaviour; (3) predicting how grassland composition would respond to global‐change manipulations if influenced only by herbivore consumption preferences; and (4) comparing these predictions to observed responses of grassland community composition to simulated global changes. Gastropod herbivores consume nearly half of aboveground production in this system. Global changes induced species‐specific changes in plant leaf characteristics, leading gastropods to alter the relative amounts of different plant types consumed. These changes in gastropod feeding preferences consistently explained global‐change‐induced responses of functional group abundance in an intact annual grassland exposed to simulated future environments. For four of the five global change scenarios, gastropod impacts explained > 50% of the quantitative changes, indicating that herbivore preferences can be a major driver of plant community responses to global changes.

Interactive effects of elevated CO2, N deposition and climate change on plant litter quality in a California annual grassland - Hugh A. L. Henry; Elsa E. Cleland; Christopher B. Field; Peter M. Vitousek (Oecologia, 2005)